Explaining Attitudes towards Immigration: New Pieces to the Puzzle - Ingrid Tucci (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
This paper deals with two hypotheses about factors influencing attitudes toward immigration in Germany. The first looks at how individuals? perceptions of their financial and job situation affect public opinion on immigration. The second hypothesis tests how these attitudes are affected by the beneficial/detrimental effect of immigration on the individual and constitutes the paper?s central contribution to the literature. The findings presented here offer direct evidence through the use of data from the German Socio-Economic-Panel (SOEP), in contrast to the indirect measures such as education and income employed in most empirical tests to date.
Keywords: 330; SOEP; immigration; opinion formation; self-interest